Optimalisasi Penggunaan Metode Pembelajaran Learning Cycle “5E” dan Artikulasi Terhadap Peningkatan Hasil Belajar Peserta Didik - Suherman, Ade (Universitas Pendidikan Indonesia, 2018)
AbstractLearning outcomes are a component that cannot be separated from learning and is used as a benchmark to determine the extent of the success of learning. High and low student learning outcomes are influenced by several factors, including the application of learning methods. The research method used was Quasi Experiment. The study was conducted with the object of research consisting of 2 experimental classes, namely class X-1 as experimental class 1 as many as 19 people and class X-5 as experimental class 2 as many as 19 people. The researcher applied the Learning Cycle method